2016
DOI: 10.1038/nn.4361
|View full text |Cite
|
Sign up to set email alerts
|

The Human Connectome Project's neuroimaging approach

Abstract: Non-invasive human neuroimaging has yielded many exciting discoveries about the brain. Numerous methodological advances have also occurred, though inertia has slowed their adoption. This paper presents an integrated approach to data acquisition, analysis, and sharing that builds upon recent advances, particularly from the Human Connectome Project (HCP). The “HCP-style” paradigm has seven core tenets: (1) collect multimodal imaging data from many subjects; (2) acquire data at high spatial and temporal resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
880
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 958 publications
(935 citation statements)
references
References 116 publications
11
880
0
2
Order By: Relevance
“…Studies have shown that surface-constrained analyses: improve the localisation of functional units along the cortical surface Glasser et al, 2013Glasser et al, , 2016bVan Essen et al, 2012); reduce the mixing of white and grey matter fMRI signals during smoothing (Glasser et al, 2013); and increase the alignment of functional areas during registration (Durrleman et al, 2009;Fischl et al, 1999c;Lombaert et al, 2013;Robinson et al, 2014;Wright et al, 2015;Yeo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that surface-constrained analyses: improve the localisation of functional units along the cortical surface Glasser et al, 2013Glasser et al, , 2016bVan Essen et al, 2012); reduce the mixing of white and grey matter fMRI signals during smoothing (Glasser et al, 2013); and increase the alignment of functional areas during registration (Durrleman et al, 2009;Fischl et al, 1999c;Lombaert et al, 2013;Robinson et al, 2014;Wright et al, 2015;Yeo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Important topics include false positives, false negatives, test-retest reliability and acquisition protocols (de Reus and van den Heuvel, 2013;Eklund et al, 2016;Glasser et al, 2016;Zuo and Xing, 2014). However, an in-depth discussion of these methodological considerations falls beyond the scope of this review.…”
Section: Methodsological Considerationsmentioning
confidence: 99%
“…In many ways still the gold standard, it is hard to scale to multiple scans (especially for modern studies running into the thousands of participants) 5,6 and multiple brain regions. Thus, the primary use of manual volumetry is in smaller studies with a single, focused hypothesis, as well as for the creation of datasets to be incorporated into automatic segmentation algorithms.…”
Section: Macro-and Meso-scopic Neuroanatomymentioning
confidence: 99%